Biosensors for the detection of Mycobacterium tuberculosis: a comprehensive overview. (2nd November 2022) - Joshi, Hemant; Kandari, Divya; Maitra, Subhrangsu Sundar; Bhatnagar, Rakesh
Abstract: Tuberculosis (TB) infection is one of the leading causes of death in the world. According to WHO reports 2019, the average rate of decrease in global TB incidences was only 1.6% per year from 2000 to 2018, besides that the global decline in TB deaths was just 11%. Therefore, the dire need for early detection of the pathogen for the successful diagnosis of TB seems justified. Mycobacterium tuberculosis secretory proteins have gained more attention as TB biomarkers, for the early diagnosis and treatment of TB. Here in this review, we elaborate on the recent advancements made in the field of piezoelectric, magnetic, optical, and electrochemical biosensors, in addition to listing their merits and setbacks. Additionally, this review also discusses the construction of biosensors through modern integrated technologies, such as combinations of analytical chemistry, molecular biology, and nanotechnology. Integrated technologies enhance the detection for perceiving highly selective, specific, and sensitive signals to detect M. tuberculosis . Furthermore, this review highlights the recent challenges and scope of improvement in numerous biosensors developed for rapid, specific, selective, and sensitive detection of tuberculosis to reduce the TB burden and successful treatment. Graphical Abstract: UF0001